Investigation On The Effect Of Dry Turning On AISI 305 Steel With Ceramic Inserts By Analysis Of Workpiece Surface Profile - Mohamad, Nurnadia Azwa (Universiti Sains Malaysia, 2018)
This research presents the dry turning machining to observe the workpiece profile of the AISI 305 by adopting ceramic insert as a cutting tool. The machining was conducted fifth passes throughout the experiment using same specimen and cutting insert. The image of ceramic insert before machining and after every each pass of machining were captured under Scanning Electron Microscope (SEM) to observe the performance during machining operation. The image of workpiece is captured by using high resolution of DSLR camera with assistant of backlighting to obtain high quality of workpiece profile. Appropriate setting of backlighting is significant to obtain a good quality of image processing. The image of the workpiece will be extracted into simulation programming to obtain the autocorrelation profile. From the autocorrelation function profile, the surface profile will be observed to detect the gradual wear of tool. The workpiece surface profile is examined using stylus and vision method to verify the profile. Vision method is the most accurate measurement method compared to stylus due to some limitations of the equipment.